2019
DOI: 10.3389/fped.2019.00204
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload and Kidney Injury Score as a Predictor for Ventilator-Associated Events

Abstract: Objective: The Pediatric and Neonatal Working group developed new ventilator associated events (VAE) definitions for children and neonates. VAE includes ventilator-associated condition (VAC), infection-related ventilator-associated complication (IVAC), and ventilator-associated pneumonia (VAP). Acute kidney injury (AKI) and fluid overload (FO) have been associated with worse clinical outcomes of ventilated children. Fluid Overload and Kidney Injury Score (FOKIS) is an automatically calculated score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…In a recent prospective study of over 4000 children admitted to pediatric intensive care units (PICUs) across four continents, AKI developed in 26.7% of children of whom 5.8% required renal replacement therapy (RRT) [2], with modalities including peritoneal dialysis, hemodialysis, and continuous RRT (CRRT). Pediatric AKI is associated with prolonged critical care admissions, greater mechanical ventilation needs, and longer overall hospitalizations [3][4][5]. The incidence of chronic kidney disease after pediatric AKI is as high as 20-50% with 10-12% of children requiring chronic dialysis within 5 years after hospital discharge [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent prospective study of over 4000 children admitted to pediatric intensive care units (PICUs) across four continents, AKI developed in 26.7% of children of whom 5.8% required renal replacement therapy (RRT) [2], with modalities including peritoneal dialysis, hemodialysis, and continuous RRT (CRRT). Pediatric AKI is associated with prolonged critical care admissions, greater mechanical ventilation needs, and longer overall hospitalizations [3][4][5]. The incidence of chronic kidney disease after pediatric AKI is as high as 20-50% with 10-12% of children requiring chronic dialysis within 5 years after hospital discharge [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to literature that demonstrates a positive correlation between AKI and FO. 15,17,22,23 This could be because we did not include the KDIGO UO criteria to define and stage AKI, and/or the rise of SCr may have been blunted by hemodilution effects, thus leading to the underdiagnosis of AKI. In the cardiac surgery population, Basu et al revealed an increase in incidence and staging of AKI in infants after correcting SCr for the effects of FO and hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies utilizing one or more of these interventions in adult ICU patients have shown significant decreases in VAE rates. However, a “bundle” of these interventions to fully optimized VAE prevention has not occurred in adults or been similarly identified for children 20 …”
Section: Ventilator‐associated Eventsmentioning
confidence: 99%